'This is Not Our Life, It's Just a Copy of Other People's': Bedu and the Price of 'Development' in South Sinai. (1st December 2011) - Gilbert, Hilary
Abstract : This study demonstrates the unplanned outcomes of development in an indigenous population, and the particular impact of prescribed development on bedouin livelihoods in South Sinai. In the latter half of the twentieth century, Bedu across the Middle East have adapted their livelihood strategies to the more or less authoritarian modernizing policies of nation-states. In South Sinai, in response to the rule of both Israeli and Egyptian regimes, the economy of local Bedu has shifted from pre-development, agropastoral livelihoods that provided subsistence for ten months a year, to an almost complete dependence on insecure paid work. Using data on bedouin livelihoods and household economics spanning more than forty years, I argue that state-led 'development' has brought very mixed blessings to its population. I demonstrate bedouin poverty –currently unacknowledged by the Egyptian state – for the first time, and show the relative inequality of Bedu compared to other Egyptian citizens. The failure of government to record bedouin experience creates a policy blind spot, ensuring their inequality persists.